Design, Synthesis, Characterization, Biological Activity and ADME Study of New 5-arylidene-4-Thiazolidinones Derivatives Having - Duha E. Taha; Ayad M.R Raauf; Karima F. Ali (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
New series of Nabumetone containing 5-arylidene-4-thiazolidinones pharmacophore as in compounds 3(a-e) were designed and synthesized by using nabumetone and hydrazinethiocarboamide to synthesize compound (1) (Schiff base), next step